The haunting quality of racism - Durrheim, Kevin; Murray, Amy Jo (PINS-Psychology in Society, 2022)
Anti-racism has nurtured many visions of post-racism futures. All this talk and political action relies on and reproduces discourses of racism. While much of this discursive force lies in what is said, we argue that a haunting quality of racism may arise from what is unsaid. This includes the multifarious points of connection between the present and the past. We are all implicated, albeit unevenly. This article describes the phenomenon of spectral racism that arises from such implicature. We develop a discursive account of its constitution in acts of dialogical repression, and we consider some of the social psychological and political ramifications of haunting racism. We illustrate our arguments by an analysis of the way the prohibition against the use of the k-word echoes the toxic past and zombifies racism via psychological enticement.